The Gingerbread Girl goes animal crackers - Ernst, Lisa Campbell (Dutton Childrens Books, 2011)
The Gingerbread Girl, who once escaped the fox that devoured her brother, must now try to save from a similar fate the animal crackers she received as a birthday gift.